Substituting steam-flaked corn with distiller’s grains alters ruminal fermentation and diet digestibility - S. Uwituze; G.L. Parsons; M.K. Shelor; K.K. Karges; M.L. Gibson; Brandon E. Depenbusch; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2008)
Rapid expansion of fuel ethanol production in the High Plains, where feedlots commonly use steam-flaked corn diets, has popularized substituting dried distiller's grains with solubles (DDGS) for a portion of the steam- flaked corn. Most of the starch in corn is removed during ethanol production. The residual material is rich in fiber, ruminal undegradable protein, and fat. Adding roughage to high-concentrate finishing diets helps maintain ruminal function by stimulating salivation, rumination, and gut motility. The source and level of roughage can influence dry matter intake. Our objective was to examine ruminal fermentation characteristics and diet digestibility when steam-flaked corn-based finishing diets were fed with either 0 or 25% DDGS, using alfalfa hay or corn silage as roughage sources.
Keywords: Cattlemen& #x27; s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Steam-flaked corn; DDGS